2019
DOI: 10.21037/qims.2019.03.06
|View full text |Cite
|
Sign up to set email alerts
|

Real-time intraoperative ultrasound in brain surgery: neuronavigation and use of contrast-enhanced image fusion

Abstract: Ganau et al. Real-time intraoperative ultrasound in brain surgery qims.amegroups.com Ganau et al. Real-time intraoperative ultrasound in brain surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 64 publications
(71 reference statements)
0
35
0
4
Order By: Relevance
“…Patients may present with hemiparesis and aphasia [30]. In an attempt to salvage neurological function, various techniques for projectile retrieval have been attempted including endovascular suction with emergency extracranial-intracranial bypass [30, 32].…”
Section: Effects Of Direct Intracranial Injurymentioning
confidence: 99%
“…Patients may present with hemiparesis and aphasia [30]. In an attempt to salvage neurological function, various techniques for projectile retrieval have been attempted including endovascular suction with emergency extracranial-intracranial bypass [30, 32].…”
Section: Effects Of Direct Intracranial Injurymentioning
confidence: 99%
“…Intraoperative B-mode ultrasound is a safe, convenient, and effective imaging tool for intraoperative monitoring that has been widely used in neurosurgery. Studies have shown that intraoperative ultrasound monitoring can help neurosurgeons locate intraoperative tumors, guide surgery, and identify residual tumors (13)(14)(15), and its application has also been found to help improve the postoperative quality of life of glioma patients (16,17). However, there are few studies on the classification of glioma by intraoperative B-mode ultrasound.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, neuronavigation integrated with high resolution tridimensional intraoperative ultrasonography addresses both common problems during tumor resection: location before craniotomy and resection control, respectively. 30 But studies comparing these combined approaches with the use of each alone are lacking.…”
Section: Discussionmentioning
confidence: 99%